Ion size effects on the dielectric and electrokinetic properties in aqueous colloidal suspensions. (August 2016) - López-García, J.J.; Horno, J.; Grosse, C.
Abstract: One of the main assumptions of the classical theory most widely used to characterize electrokinetic phenomena is that ions behave as point-like entities. While the realization of the importance of the finite ion size goes back to Stern, 1924, it was Bikerman who presented in 1942 the first expression for the steric interactions among ions. Even now, this is the most often used expression, mainly due to its analytic simplicity. However, once ions are considered to have a finite size, other consequences besides the steric interactions have to be considered. For example, the finite closest approach distance of ions to the interface, the dielectrophoretic force acting on ions in a non-uniform electric field, the variation of the electrolyte solution permittivity with the local ion concentration, and the corresponding Born force acting on the ions, have to be taken into account. In this work, we examine these items in detail and discuss the main contributions made in this field. They show that even for the relatively low surface charge and electrolyte concentration values encountered in colloidal suspension studies, corrections to the classical theory due to ion size effects are far from negligible. Graphical abstract: Highlights: Corrections to the classical theory due to ion size effects are far from negligible. Steric interactions increase the mobility, conductivity increment, and low-frequency dielectric dispersion amplitude. Carnahan–Starling leads to substantial corrections for system parameter values typical for colloidal suspensions. Even stronger corrections are obtained when Carnahan–Starling is combined with the representation of ions as dielectric spheres.